Teacher-Student Interaction Models: Effective Strategies for Increasing Student Participation and Motivation - Sinaga, Dameria (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Effective teacher-student interactions are pivotal in fostering an engaging and motivating learning environment. Despite recognizing their importance, educators often seek evidence-based strategies to enhance student participation and motivation consistently. This study identifies and evaluates various teacher-student interaction models to determine their effectiveness in increasing student participation and motivation within diverse educational settings. Employing a quantitative methods approach, the research involved 150 teachers and 1,200 students across multiple secondary schools in East Jakarta Indonesia. Quantitative data were collected through structured surveys measuring student engagement and motivation levels, while qualitative insights were garnered from semi-structured interviews and classroom observations. Statistical analyses, including ANOVA and regression models, were utilized to assess the impact of different interaction strategies. Thematic analysis was conducted on qualitative data to identify recurring patterns and contextual factors influencing outcomes. The findings indicate that interaction models emphasizing collaborative learning and personalized feedback significantly enhance student participation and motivation. Specifically, strategies such as the Socratic Method and Flipped Classroom demonstrated a 25% and 30% increase in student engagement metrics, respectively. Additionally, the integration of technology-mediated interactions was found to foster higher levels of student motivation compared to traditional instructional methods. Qualitative data revealed that teachers' interactive and student-centered approaches made students feel more valued and empowered.